2015
DOI: 10.1007/s00404-015-3659-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of leptin and IP-10 in preeclampsia compared to controls

Abstract: The results of the present study support a significant role of leptin in PE; however, this association was independent from serum IP-10 levels, suggesting that there is no crucial interplay between these two proteins in PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…The increased risk of pre‐eclampsia and GDM with higher leptin levels are consistent with several other studies . In previous studies, leptin levels during pregnancy were observed to be higher among women with pre‐eclampsia compared with controls, though no previous studies assessed levels prior to pregnancy and subsequent pre‐eclampsia. Interestingly, women with gene polymorphisms on the leptin receptor gene (LEPR) were also more likely to develop severe pre‐eclampsia .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increased risk of pre‐eclampsia and GDM with higher leptin levels are consistent with several other studies . In previous studies, leptin levels during pregnancy were observed to be higher among women with pre‐eclampsia compared with controls, though no previous studies assessed levels prior to pregnancy and subsequent pre‐eclampsia. Interestingly, women with gene polymorphisms on the leptin receptor gene (LEPR) were also more likely to develop severe pre‐eclampsia .…”
Section: Discussionsupporting
confidence: 90%
“…Given the strong positive association between high leptin levels and body mass index (BMI) and body fat mass, leptin may mediate the link between the increased risk of pregnancy complications in women with obesity. Leptin has been associated with pre‐eclampsia, gestational diabetes (GDM), higher rates of neonatal morbidity, mortality, and neonatal ICU admissions in the offspring . However, studies evaluating the relations between leptin and pregnancy outcomes have included only a small number of women and measured leptin levels during pregnancy, which cannot rule out reverse causality.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some promising predictive biomarkers, none of them has yet proven to be sensitive and specific enough for clinical practice [26][27][28]. If diagnosed early and managed properly, HELLP syndrome in most patients usually starts to improve within the first 24-48 h after delivery [29].…”
Section: Discussionmentioning
confidence: 98%
“…Involvement of leptin in pathogenesis of PE has been previously investigated. A study reported that, PE is considered an exaggerated inflammatory condition in which leptin inhibits the generation and proliferation of T-regulatory cells and induces the Th-17 cells responsible for activation of the inflammatory reaction (12). Leptin also, mediates the production of pro-inflammatory cytokines like TNF-α and IL-6 in PE inducing maternal vascular and renal pathology that provoke hypertension and proteinuria (25).…”
Section: Discussionmentioning
confidence: 99%
“…The ischemic placental hypoxia stimulates the release of different dysfunctional factors, particularly from the renal tissue eliciting maternal hypertension and proteinuria in PE. Severe oxidative stress (OS) and the release of various maternal and placental factors are the main players inducing endothelial dysfunction which is the crucial event in pathophysiology of PE (12). Addition of severe OS induced by PE to its already elevated level due to a high altitude (HA) residence could accentuate the release of these placental and maternal factors causing more severe maternal endothelial dysfunction that increases the prevalence of this condition in HA resident pregnant women.…”
Section: Introductionmentioning
confidence: 99%